Asymmetric Synthesis of Axinellamines A and B. (8th March 2016) - Ma, Zhiqiang; Wang, Xiao; Ma, Yuyong; Chen, Chuo
Abstract: Axinellamines A and B are broad‐spectrum antibacterial pyrrole–imidazole alkaloids that have a complex polycyclic skeleton. A new asymmetric synthesis of these marine sponge metabolites is described herein, featuring an oxidative rearrangement and an anchimeric chlorination reaction. Abstract : Von Natur aus reich an Stickstoff : Axinellamin A und B sind zwei dimere Pyrrol‐Imidazol‐Alkaloide mit ungewöhnlich hohem Anteil an Stickstoff‐ und Halogenatomen. Eine asymmetrische Synthese für die komplizierten Strukturen dieser natürlichen Antibiotika wird vorgestellt.